Development of ultrasound imaging CAD tool for assessment of pathologies in supraspinatus tendon - Gupta, R. (IGI Global, 2016)
Non-invasive diagnostic imaging methods for diagnosis of pathological conditions is increasingly gaining popularity resulting from speedy and effective recovery during follow up in several clinical trials. The accuracy of the diagnosis depends on the experience and knowledge of physicians conducting the trial. In such scenario, the need for quantitative measures for details such as shape and size of tissue can assist physicians for better intuitive understanding of tissue and its pathologies. Computer aided diagnosis (CAD) tool incorporating methods for segmentation, texture analysis and area computation can increase the accuracy of diagnosis by providing quantitative analysis of the image. This chapter briefly describes issues and challenges for building the CAD tool followed by brief description about the methods involved. The methods are validation are also discussed briefly. To summarize the work, brief discussion about a new software or CAD tool for diagnosis of pathologies supraspinatus tendon with the help of ultrasound images is provided. The new software has an intuitive user interface which is easy, quick and suitable for medical work. Â© 2017 by IGI Global. All rights reserved.